The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.3109/19401736.2013.840591
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial DNA diversity in the African American population

Abstract: Genetic polymorphism along mitochondrial DNA (mtDNA) defines population-specific signatures called mtDNA haplogroups. Estimation of mtDNA haplogroup distribution may be prone to errors, notably if the study sample is not drawn from a multicenter cohort. Here, we report on mtDNA diversity in a sample of African American individuals (n = 343) enrolled in a multicenter cohort. Sequencing of the hypervariable regions I and II of the D-loop control region showed that the most common mitochondrial variants are 73G, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 27 publications
(48 reference statements)
0
15
2
Order By: Relevance
“…L2 for L2a) represented the majority of the observed ambiguities (about 7%); with the adopted grouping procedure, these haplogroups felt under the same macrohaplogroups. As reported in the early study [20], about 2.9% of self-reported Caucasian descents were re-classified by PCA as African American descents.…”
Section: Resultsmentioning
confidence: 91%
See 4 more Smart Citations
“…L2 for L2a) represented the majority of the observed ambiguities (about 7%); with the adopted grouping procedure, these haplogroups felt under the same macrohaplogroups. As reported in the early study [20], about 2.9% of self-reported Caucasian descents were re-classified by PCA as African American descents.…”
Section: Resultsmentioning
confidence: 91%
“…Principal component analysis (PCA) based on a validated set of 150 nuclear AIMs typed in the predominantly African American REACH cohort previously enabled us to identify and exclude study participants of admixed population descent, namely, other than non-Hispanic African or European descent [20]. In that study ( n =343), from which the present study sample was derived, we observed 17 out of the 18 mtDNA haplogroups reported so far for populations of African American descent, indicating a good representation of the African American population diversity in our studied REACH sample.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations